39 Overview of Recipient Site Creation (Hair Transplantation, 2023)
One of the critical steps in determining the outcome of a hair transplant procedure is the creation of the recipient site incisions. When learning to make these, there are several key principles involved, including correct and appropriate determination of incision size and shape, depth, angle, direction, density, and geometry. Recipient sites can be premade before starting to place grafts or can be made at the same time as each graft is placed. There are a wide variety of instruments that are used to make recipient site incisions, including blades, needles, and implanters. Multi-incision instruments can be used to potentially increase the speed of site making and robotic technology can be used to eliminate any human fatigue element.
Keywords: hair transplant recipient sites; hair transplant incisions; size; shape; depth; angle; direction; density; geometry